A sulfonated polyethylene–styrene cation exchange membrane: a potential separator material in vanadium redox flow battery applications. (31st January 2022) - Sreenath, Sooraj; Pawar, Chetan M.; Bavdane, Priyanka; Nikumbe, Devendra Y.; Nagarale, Rajaram K
Abstract : Benchmarking of a polyethylene–styrene–divinylbenzene-based interpolymer cation exchange membrane for vanadium redox flow batteries. Abstract : We report on the synthesis and characterization of a polyethylene–styrene–divinylbenzene-based interpolymer cation exchange membrane (ICEM) and its applicability as a separator in a vanadium redox flow battery (VRFB). The ICEM preparation involved radical co-polymerization of styrene–divinylbenzene in molten polyethylene and then blow film extrusion and sulfonation using chlorosulfonic acid. The crossover of vanadium ions across ICEM was studied in a charge balanced two-compartment cell and its efficacy was comparable to that of Nafion®117. Further study evaluated the chemical, dimensional, and mechanical stability in a highly oxidative environment of 2.1 M H2 SO4 and 1.6 M VO2 + ions over 30 days at 50 °C. The VRFB performance exhibited 95% Coulombic, 63% energy, and 67% voltage efficiencies at 140 mA cm −2 over 100 charge/discharge cycles. The polarization curve indicated an operational power density of 310 W cm −2 at a limiting current density of 350 mA cm −2, revealing a low membrane resistivity. An asymmetric flow battery was set up to overcome VRFB capacity fading and operated at 100 mA cm −2 . The study demonstrated the superiority of ICEM over Nafion®117 in terms of self-discharge and capacity retention under identical operational conditions. The findings of this study indicated long-term operational stability of ICEM and suitability in VRFB applications.